2022
DOI: 10.1186/s12933-022-01727-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating level of β-aminoisobutyric acid (BAIBA) in heart failure patients with type 2 diabetes receiving sodium-glucose cotransporter 2 inhibitors

Abstract: Aims The mechanism by which a sodium-glucose cotransporter inhibitor (SGLT2i) induces favorable effects on diabetes and cardiovascular diseases including heart failure (HF) remains poorly understood. Metabolomics including amino acid profiling enables detection of alterations in whole body metabolism. The aim of this study was to determine whether plasma amino acid profiles are modulated by SGLT2i use in HF patients with type 2 diabetes mellitus (T2DM). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…SGLT2 inhibitors have been suggested to prevent kidney fibrosis, podocyte injury and apoptosis of glomerular cells by increasing protective adipokine expression, such as adropin, irisin and apelin, which act directly through the activation of Akt/STAT3 and tyrosine protein kinase JAK2 (JAK2)/signal transducer pathways. 34,45,48,51,52 Finally, SGLT2 inhibitors adapt metabolic homeostasis by mediating the activity of NADPH oxidase and transcription factors (nuclear factor-κB and nuclear factor erythroid 2-related factor 2) preventing advanced glycation and autophagy. 51,52 These effects are considered to be crucial in the treatment of patients with either T2DM- or non-T2DM-related CKD who have HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SGLT2 inhibitors have been suggested to prevent kidney fibrosis, podocyte injury and apoptosis of glomerular cells by increasing protective adipokine expression, such as adropin, irisin and apelin, which act directly through the activation of Akt/STAT3 and tyrosine protein kinase JAK2 (JAK2)/signal transducer pathways. 34,45,48,51,52 Finally, SGLT2 inhibitors adapt metabolic homeostasis by mediating the activity of NADPH oxidase and transcription factors (nuclear factor-κB and nuclear factor erythroid 2-related factor 2) preventing advanced glycation and autophagy. 51,52 These effects are considered to be crucial in the treatment of patients with either T2DM- or non-T2DM-related CKD who have HF.…”
Section: Discussionmentioning
confidence: 99%
“…34,45,48,51,52 Finally, SGLT2 inhibitors adapt metabolic homeostasis by mediating the activity of NADPH oxidase and transcription factors (nuclear factor-κB and nuclear factor erythroid 2-related factor 2) preventing advanced glycation and autophagy. 51,52 These effects are considered to be crucial in the treatment of patients with either T2DM- or non-T2DM-related CKD who have HF. 53,54 Yet, SGLT2 inhibitors have been postulated, through their capability to change ketogenetic energy, to suppress inflammation and oxidative stress, enabling the mediation of several modalities of endogenous tissue protection, which include the enhancement of mitochondrial function and reduction of reactive oxygen species production.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in BAIBA in plasma or urine is also associated with fatty liver disease in other species, such as geese, and type 2 diabetes in humans. [28][29][30][31] BAIBA is mainly secreted by skeletal muscles, but levels are regulated by hepatic mitochondrial enzymes and are associated with important effects on carbohydrate and lipid metabolism. 31 An increase in BAIBA may also be related to alterations in other amino acid metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics is an emerging systems biology technology that can be utilized to explore new biomarkers for disease detection and identify metabolic pathways associated with disease etiology [20]. Prior research has indicated that SGLT2 inhibitors can significantly affect the level of circulating metabolites, especially those related to lipids, amino acids, and ketone bodies [21][22][23]. Besides, mutations resulting in SGLT1 dysfunction may modify intestinal homeostasis and promote favorable metabolic outcomes [24,25].…”
Section: Introductionmentioning
confidence: 99%